The Effect of Allogenic Bone Marrow Mesenchymal Stem Cell - Platelet Rich Plasma (Bmscs - Prp) Intra-Articular Injection Effect on the Regeneration of Full-Thickness Joint Cartilage Defect on Rabbit - Ahmad Taufik.S1, Dwikora Novembri Utomo2, Hari Basuki Notobroto3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Full thickness cartilage defects are still a problem until present since the handling has not give any satisfactory results. Current handling is performed through cartilage enginering using mesenchymal stem cells alone and or in combination with growth factor. The purpose of this study was to investigate the effect of injection of intra-articular injection of Allogenic bone marrow mesenchymal stem cell - Platelet rich plasma (BMSCs-PRP) on regeneration of full thickness cartilage defect in rabbits. Method: The design of this study is a post-test only control group design using 36 New Zealand white rabbits divided into three groups treated with PRP, BMSCs and BMSCs-PRP. Results are evaluated after 10 weeks. Results: In the evaluation, macroscopic images showed the best healing in the BMSCs-PRP group. Histopathologic examination showed that in the MSCs-PRP group there was a significant increase in the amount of chondrocytes (p = 0.000), cartilage area (p = 0.000), as well as the number of Agecoprogenitor expec- tion cells (p = 0.000) and type 2 collagen (p = 0.000). Conclusions: Intra-articular injections Allogenic bone marrow mesenchymal stem cell (BMSCs-PRP) is able to regenerate and cure full-thickness joint cartilage defects through differentiation of MSCs into condroblasts.